Statistical design and analysis of experiments : with applications to engineering and science - Mason, Robert L. 1946- (J. Wiley, 2003)
Practicing engineers and scientists often have a need to utilize statistical approaches to solving problems in an experimental setting. Yet many have little formal training in statistics. Statistical Design and Analysis of Experiments gives such readers a carefully selected, practical background in the statistical techniques that are most useful to experimenters and data analysts who collect, analyze, and interpret data.
Keywords: Engineering -- Statistical methods.; Science -- Statistical methods.; Experimental design.; Experimental design -- Statistical methods.; elektronické knihy; electronic books